Physical fitness profile of high-level female Portuguese handball players - Rios, M.; Fernandes, R. J.; Cardoso, R.; Monteiro, A. S.; Cardoso, F.; Fernandes, A.; Silva, G.; Fonseca, P.; Vilas-Boas, J. P.; Silva, J. A. (International Journal of Environmental Research and Public Health, 2024)
We characterized the physical and physiological profiles of high-level female Portuguese handball players and examined the relationships between their anthropometric characteristics, general motor performance and cardiopulmonary fitness. Twenty-four high-level female handball players with an average age of 23.6 ± 5.5 years, height of 173.6 ± 5.1 cm and body mass of 72.6 ± 9.1 kg volunteered to participate. A Pearson correlation test was used to assess the relationship between variables. Direct relationships were observed between the players` height and arm span (r = 0.741), as well as between their squat jump and countermovement jump performances with regard to body mass (r = 0.448 and 0.496, respectively). The 9 m jump shot has a large relationship with the 7 m standing throw (r = 0.786) and between left hand dynamometry and body mass index (r = 0.595). The 30 m sprint has a relationship with the 7 m standing throw (r = -0.526) and the 9 m jump throw (r = -0.551). Oxygen uptake has a relationship with the players` height (r = -0.482) and time limit (r = 0.513), while the fitness index has a relation to the players` height (r = -0.488) and arm span (r = -0.422). Our results should be considered when using physical testing to plan optimal physical training regimens in elite team handball.